Revitalisasi Organisasi Tranformasi Birokrasi Menuju Profesionalisme Unggul Dalam Akuntansi Keprilakuan - Eko Cahyo Mayndarto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The transformation of bureaucracy towards professionalism is a critical journey in increasing organizational efficiency and effectiveness. In an era of global dynamics and increasingly complex societal demands, the bureaucracy must adapt to meet high standards of professionalism. This research explores strategies and concrete steps that can be implemented to strengthen professionalism in a bureaucratic environment. First, this research analyzes the role of technology and innovation in increasing bureaucratic operational efficiency, enabling more responsive and connected system integration. Furthermore, the focus on developing competencies and skills involves developing human resources that are oriented towards professionalism. Establishing an organizational culture that promotes ethics, transparency and accountability is also an important focus in stimulating positive change. The research results show that through a combination of these strategies, the bureaucracy can achieve higher professionalism, improve services to the community, and build trust as the main pillar in organizational governance. In conclusion, transformation towards professionalism is not only a necessity, but also an opportunity to improve service quality and answer complex challenges in an ever-changing world